Youth, Europe and the Nation: The political knowledge, interests and identities of the new generation of European youth - Faas, Daniel (My University, 2007)
Europe is undergoing considerable demographic, economic, cultural and socio-political change. National citizenship identities have been challenged by the simultaneous processes of European integration and the migration of people into and across Europe. This paper explores how the current generation of youth relates towards Europe, and highlights the factors affecting their political knowledge, interests and identities. Although the article draws on mainly qualitative data from a study into the political identities of native youth and youth of Turkish descent in England and Germany, the results have implications for all European countries [1]. The research indicates that, in countries which promote European agendas and where schools and curricula emphasise an inclusive concept of Europe (e.g. Goethe Gymnasium in Stuttgart), young people have high levels of knowledge about Europe and make Europe part of their hybrid identities. However, in countries where governments and schools marginalise European agendas (e.g. Millroad School in London), young people struggle to relate positively to Europe, especially in working-class contexts where national(istic) agendas come to the fore. The article raises important questions about the possibilities of promoting inclusive governmental and curriculum approaches and offers ways in which the knowledge and identity gaps between youth in different European countries could be addressed.
PUBLISHED
Keywords: Youth; Integration; Identities in Transformation; Inclusive Society; International Integration